PARAMETRIC ANALYSIS OF A SAWDUST-POWERED BIOMASS CHP SYSTEM: EFFECTS ON SUSTAINABILITY AND PERFORMANCE - Panahirad, Behzad; Dalirazar, Mohammadreza; Dost, Danial Moghadam; Jafarieh, Amirsalar; Aminian, Saman; Zarei, Kavan (Begell House Inc., 2025)
In this research study, we focused on a biomass-powered combined heat and power (CHP) system encompassing multigeneration purposes. The system was comprised of a combustion chamber, single-effect absorption cooling system, air conditioning unit, reheat steam Rankine cycle, organic Rankine cycle, and electrolyzer. Biofuel, namely, pine sawdust, was selected for the combustion process. Parametric analysis was also conducted for various parameters, including the ambient temperature, bio-fuel flow rate, and boiler outlet temperature. It was determined that the energy efficiency and overall utilization factor of the CHP plant were 2.096 and 24.03%, respectively. The analysis revealed an approximate sustainability index (SI) of 1.32 and specific carbon dioxide emissions of 354 kg/(MW·h). The results from the parametric studies indicated that the system’s sustainability improved as the mass flow rate of the biofuel increased; specifically, increasing the biofuel mass flow rate by 0.097 kg/s increased the SI index by 0.233. However, any increase in the boiler and sink outlet temperatures led to a decrease in the SI, indicating a negative impact on the system’s environmental performance. © 2025 by Begell House, Inc.
Keywords: exergy analysis; irreversibility; parametric analysis; sawdust; sustainability index